Chemical characterization of “Alcaparras” stoned table olives from Northeast Portugal - Sousa, Anabela (2011)
Commercial stoned table olives named "alcaparras" from Trás-os-Montes (Portugal) were chemically characterized. During three consecutive years (2004-2006) 30 samples (10 per year) were examined for their nutritional value (moisture, crude protein, total fat, ash, carbohydrates, and energy), with a detailed report of the fatty acids and tocopherols composition. Water was the major constituent (72.5 ± 5.5%), followed by fat (14.6 ± 5.1%). The average amount of protein and ash were 1.1% and 3.4%, respectively, reporting unusual ash values for table olives, related to the technological process. One hundred grams of fresh stoned table olives presented an average energetic value of 156 kcal, lower than most table olives. The lipids are rich in oleic acid (average of 77.7 ± 2.0%), followed by palmitic acid and linoleic acid. Samples showed an average of total tocopherols of 1.2 mg/100 g of fresh weight, being α-tocopherol the most abundant. Table olives are important sources of MUFA, as olive oil, recognized as a preventive factor in diseases in which free radicals are implicated, complemented by the amounts of vitamin E, with both antioxidant and vitamin action.